Poly (methyl vinyl ether-alt-maleic anhydride) as an ecofriendly electrolyte additive for high-voltage lithium-rich oxides with improved stability of interphase. (20th December 2021) - Ma, Xin; Wang, Man; Qian, Yunxian; Feng, Dongyu; Zhang, Guangzhao; Xu, Dongwei; Kang, Yuanyuan; Liu, Zhongbo; Hu, Shiguang; Zheng, Jiaxin; Wang, Jun; Wang, Chaoyang; et al.
Abstract: In this work, poly (methyl vinyl ether-alt-maleic anhydride) abbreviated as P(MVE-MA) is employed as an ecofriendly electrolyte additive for stabilizing the interface of high-voltage layered Li-rich oxides (LLROs) without sacrificing performance. By the addition of 1 wt. % P(MVE-MA), the capacity retention of the Li-rich oxides at 250 mA g −1 for 300 cycles in the voltage range of 2.5–4.6 V is significantly improved from 38.6% to 77.2%, and the retained specific discharge capacity is as high as 159 mAh g −1 . It is also found that the voltage decay and resistance increase during cycling are both suppressed noticeably because that the addition of P(MVE-MA) suppresses electrolyte degradation. Based on various characterizations, P(MVE-MA) mainly has two functions: one is to decrease the H2 O and HF contents in the electrolyte due to the hygroscopic property of anhydride; and the other is to form thin and stable polymer cathode electrolyte interphase (CEI) on LLROs because of its strong adhesive ability to the cathode. Therefore, the side reactions and structural degradation of LLROs are mitigated distinctly, improving the electrochemical performance of LLROs. Considering its effective and ecofriendly performance for high-voltage LLROs, P(MVE-MA) is believed to be positive for other high-voltage cathode materials. Graphical abstract: Image, graphical abstract